Health and Safety Management System, Biological Sewage Treatment Ponds in Tehama Region, Yemen - Tarik Abbas Mohammed; Afrah Alsaid-Betalfaqih; Abdul Raqib; Youser-Zabid (Indian Journal of Forensic Medicine & Toxicology, 2021)
Under the German-Yemeni Financial Co-operation Program three treatments Sewage stations have beendeveloped for the towns of Bajil, Bet Al-Faqih and Zabid in Tehama region.This present investigation work covers the following aspects ,Design and specific characteristics of thestabilisation ponds description of the existing situation, and presents analytical results for key values suchas Biological Oxygen Demand ( BOD) and Dissolved Oxygen( DO), interpretation, problem diagnosis andsuggested remedies.